Peranan Tally Man pada PT. Gelora Perkasa Belawan dalam Menunjang Kelancaran Bongkar Muat di Pelabuhan Belawan - Rendy Johanes Martin Sihombing; Suratni Ginting; Muhammad Sahid (Port Management and Maritime Administration Journal, 2026)
This study aims to analyze the role of the tally man at PT. Gelora Perkasa Belawan in supporting the effectiveness and smoothness of loading and unloading processes at Belawan Port. As the front line in cargo supervision, the tally man bears a crucial responsibility for recording the quantity, condition, and types of goods, which serve as the primary data for company reports. The research method employed is descriptive qualitative, with data collection techniques involving field observations, interviews with operational staff, and literature reviews conducted during the internship period. The findings indicate that while the tally man performs a vital function as a supervisor and data recorder, their performance is often hindered by high workloads and a limited number of personnel. The main obstacles identified include dual responsibilities, which lead to decreased data accuracy and risks of operational delays due to physical fatigue. Optimization efforts are carried out by increasing personnel during peak hours and improving accuracy in validating cargo documents. The study concludes that strengthening the tally man's role through better workload management is essential for ensuring logistical reliability and the efficient flow of goods at the port.